2019
DOI: 10.1021/acs.jafc.9b00760
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity Improvement of Pine Nut Peptides by a Pulsed Electric Field and Their Structure–Activity Relationships

Abstract: In this study, Alg-Gly-Ala-Val-Leu-His (RGAVLH) obtained from pine nut (Pinus koraiensis Sieb. et Zucc.) protein was chosen to investigate the phenomenon of immunomodulatory activity improvement upon pulsed electric field (PEF) processing. The influence of electric field intensity on immunomodulatory activity of RGAVLH was evaluated using RAW 264.7 cells. It was found that RGAVLH can not only significantly (p < 0.05) improve the capability of macrophage phagocytosis but also promote the production of nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…PEF processing could convert KWFCT structure β‐turn and random coil to each other, and KWFM structure β‐sheet, β‐turn, and random coil to each other. These were consistent with earlier reports that PEF could change the secondary structure of peptides and were shown in CD (Liang et al, 2017, 2018; Lin, Liang, Xing, et al, 2017; Lin, Liang, Xue, et al, 2017; Zhang et al, 2016; Zhang, Liang, et al, 2019). In the one‐dimensional NMR hydrogen spectrum, the active hydrogen on the peptide was shifted in many places, which was consistent with the previous research results.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…PEF processing could convert KWFCT structure β‐turn and random coil to each other, and KWFM structure β‐sheet, β‐turn, and random coil to each other. These were consistent with earlier reports that PEF could change the secondary structure of peptides and were shown in CD (Liang et al, 2017, 2018; Lin, Liang, Xing, et al, 2017; Lin, Liang, Xue, et al, 2017; Zhang et al, 2016; Zhang, Liang, et al, 2019). In the one‐dimensional NMR hydrogen spectrum, the active hydrogen on the peptide was shifted in many places, which was consistent with the previous research results.…”
Section: Resultssupporting
confidence: 92%
“…Similar studies have been published. Zhang, Liang, et al (2019)) found that the long‐range correlation between C α H at 3.39 ppm and N α H at 8.24 ppm of the PEF‐treated RGAVLH was enhanced. The space force and state of the polypeptide solution could be mirrored by the short‐range and long‐range correlation between hydrogen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations